Elevated Levels of Anti-Inflammatory Eicosanoids and Monocyte Heterogeneity in Mycobacterium tuberculosis Infection and Disease - Nore, Kristin Grotle; Jørgensen, Marthe Jøntvedt; Dyrhol-Riise, Anne Ma; Jenum, Synne; Tonby, Kristian (Frontiers in Immunology, 2020)
Eicosanoids modulate both innate and adaptive immune responses in Mycobacterium tuberculosis (Mtb) infection and have been suggested as possible Host Directed Therapy (HDT) targets, but more knowledge of eicosanoid dynamics in Mtb infection is required. We investigated the levels and ratios of eicosanoid mediators and their cellular sources, monocyte subsets and CD4 T cells in Tuberculosis (TB) patients with various clinical states of Mtb infection. Patients consenting to prospective enrolment in a TB quality registry and biorepository, 16 with pulmonary TB (before and at-end-of treatment), 14 with extrapulmonary TB and 17 latently infected (LTBI) were included. Plasma levels of Prostaglandin E2 (PGE2), Lipoxin A4 (LXA4) and Leukotriene B4 (LTB4) were measured by enzyme-linked immunosorbent assay. Monocyte subsets and CD4 T cells and their expression of Cyclooxygenase-2 (COX-2), Prostaglandin receptor EP2 (EP2) and 5-Lipoxygenase (5-LOX) were analyzed by flow cytometry with and without Purified Protein Derivate (PPD)-stimulation. Pulmonary TB patients had elevated levels of the anti-inflammatory mediator LXA4 at diagnosis compared to LTBI (p<0.01), while levels of PGE2 and LTB4 showed no difference between clinical states of Mtb infection. LTB4 was the only mediator to be reduced upon treatment (p<0.05), along with the ratio LTB4/LXA4 (p<0.01). Pulmonary TB patients had higher levels of total monocytes at diagnosis compared to end-of-treatment and LTBI (both p < 0.05), and a relative increase in the classical monocyte subset. All monocyte subsets had low basal expression of COX-2 and 5-LOX, which were markedly increased upon PPD stimulation. By contrast, the expression of EP2 was reduced upon stimulation. CD4 T cells expressed low basal COX-2 activity that increased modestly upon stimulation, whereas their basal expression of 5-LOX was considerable. In conclusion, the level of eicosanoids in plasma seem to vary between clinical states of Mtb infection. Mediators in the eicosanoid system are present in monocytes and CD4 T cells. The expression of eicosanoids in monocytes are responsive to mycobacterial stimulation independent of Mtb disease state, but subsets are heterogeneous with regard to eicosanoid-mediator expression. Further exploration of eicosanoid mediators as targets for HDT in TB are warranted.